India : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in India during 1996-98. After three successive years of growth more than 7 percent, growth of slowed to an estimated 5 percent in 1997/98. The slowdown predates the Asian crisis, and its proximate causes are a decline in agricultural output and weak industrial sales. Weaker investment appears to be a major factor behind the industrial slowdown. The balance of payments continued to improve in 1997/98, despite a widening in the current account deficit to 1 1\2 percent of GDP.